Bridge assessment reduction factors based on Monte Carlo routine with copulas. (1st November 2019) - Pérez Sifre, Sergi; Lenner, Roman
Highlights: Robust Monte Carlo simulation with bivariate copulas is a suitable tool for the investigation. Analysis of the influence of basic traffic descriptors on the load effects. Load effects reduction factors based on basic traffic descriptors. Reduced load effects suitable for assessment of bridges. Basis for assessment traffic load model for existing bridges. Abstract: The issue of assessment of existing bridges has become important over the last decades among structural engineers and authorities. Due to factors like deterioration of materials, increasing traffic loads and intensity of traffic, it is necessary to evaluate the performance of existing bridges. It is widely accepted that current design codes are not suitable for the assessment of bridges. This study is aimed at finding correlations between load effects and easily obtainable traffic descriptors such as average daily truck traffic and percentage of long vehicles that are used to modify the design traffic load model. First objective of the paper is to develop a robust Monte Carlo simulation technique by using bivariate copula functions. Such routine enables the generation of all the traffic flows necessary to assess the influence of traffic characteristics on the extrapolated load effects and as a second objective to establish design load reduction factors. The results exhibit that an assessment traffic load model based on basic traffic descriptors can be potentially used to evaluate existing bridges.